A study on the relationship between body mass index and dental caries in children at the Polyclinic, Kulliyyah of Dentistry IIUM - Faisal, Ghasak Ghazi; Ardini, Yunita Dewi; Ibrahim, Farahin; Mohd Noh, Nur Zety (2014)

(untitled)
Objective: To investigate the relationship between body mass index (BMI) and dental caries among paediatric patients attending the Polyclinic, Kulliyyah of Dentistry, IIUM. Materials and Methods: Total of 120 patients attending Paediatric Dentistry clinic, aged between 3-12 years old were included in this study. Body weight and height of the patient were measured. They were grouped according to BMI categories; underweight, normal, overweight, and obese. Dental charting was done and information regarding frequency of brushing, sugary food intake, parents’ educational level and income were obtained from the questionnaires given to the parents. Results: Out of 120 patients, 20.8% patients were underweight, 65 % normal, 5 % overweight, and 9.2 % obese. Meanwhile, 16.7% of the children had low caries risk, 20.8% medium caries risk and 62.5% high caries risk. Both underweight and overweight children showed increased prevalence of high caries risk than normal weight children. However, it is not statistically significant p>0.05 . The results showed that the age group three to five scores highest in high risk caries (69.6%) and, children with low sugary intake showed the highest percentage of low caries risk (50%). Children who do not practice tooth brushing also showed the highest caries risk (76.9%). Conclusions: Dental caries is a multifactorial disease caused by factors such as age, diet and oral self-care. Therefore, BMI can be attributed to play only a partial role in determining caries status in children. Hence, oral health education and dietary advice should be emphasized during early childhood to achieve good oral health.